Modeling the formation of TOCl, TOBr and TOI during chlor(am)ination of drinking water. (1st June 2016) - Zhu, Xiaohu; Zhang, Xiangru
Abstract: The use of chlorine and chloramines in drinking water disinfection may produce innumerable halogenated disinfection byproducts (DBPs). Because of the impossibility of measuring the concentration and evaluating the toxicity of each individual halogenated DBP in a water sample, total organic halogen (TOX) as a collective parameter and a toxicity indicator for all the halogenated DBPs has been gaining popularity in recent years. TOX can be divided into total organic chlorine (TOCl), total organic bromine (TOBr), and total organic iodine (TOI). Previously, the authors' group studied the formation kinetics of TOCl and TOBr in chlor(am)ination using two models. In this study, we further explored the formation kinetics of TOI as well as TOCl and TOBr during chlor(am)ination by carefully selecting a series of iodine-related reactions and incorporating them into the two kinetic models. The models well predicted the levels of TOCl, TOBr, TOI, and total chlorine residual during chlorination and chloramination of simulated raw waters. According to the modeling results, 57.1–73.6% of the total generated iodinated DBPs in chlorination was converted to their chlorinated and brominated analogues by the substitution with hypochlorous acid and hypobromous acid; while in chloramination, with the presence of excessive monochloramine, the formed hypoiodous acid might react with monochloramine to form an iodine-substituted intermediate (proposed as chloroiodamine), which was responsible for 41.4–49.8% of the total generated iodinated DBPs, and meantime 51.9–52.6% of the total generated iodinated DBPs underwent deiodination via the base-catalyzed hydrolysis. The models were successfully applied in determining the lag time between the dosages of chlorine and ammonia, a challenging issue in chlorine–chloramine sequential treatment. This study provided important insights into kinetic reactions that control the formation of overall halogenated DBPs in chlor(am)ination. Graphical abstract: Highlights: Two models on the TOCl, TOBr and TOI formation in chlor(am)ination were developed. The models well predicted the TOCl, TOBr and TOI levels during chlor(am)ination. The models well determined the lag time in sequential chlorination-chloramination. The models provided insights into DBPs' formation and control in chlor(am)ination.